2011
DOI: 10.1007/s10633-011-9271-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of common anesthetics on eye movement and electroretinogram

Abstract: High-resolution magnetic resonance imaging (MRI) provides non-invasive images of retinal anatomy, physiology and function with depth-resolved laminar resolution. Eye movement and drift, however, could limit high spatial resolution imaging, and anesthetics that minimize eye movement could significantly attenuate retinal function. The aim of this study was to determine the optimal anesthetic preparations to minimize eye movement and maximize visual-evoked retinal response in rats. Eye movements were examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 58 publications
3
60
2
Order By: Relevance
“…These results, although not conclusive, are in agreement with the filter characteristics. Using more animals to study each filter, evaluating the possible influence of the anesthesia, 28 and choosing filters with a more suitable transmittance curve could allow a more detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, although not conclusive, are in agreement with the filter characteristics. Using more animals to study each filter, evaluating the possible influence of the anesthesia, 28 and choosing filters with a more suitable transmittance curve could allow a more detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The ketamine/xylazine anesthetic shows robust ERGs with large a-wave and b-wave amplitudes, and low eye movements. 28 Pupils were dilated by applying a topical drop of 1% tropicamide (Colircusí Tropicamida; Alcon, Barcelona, Spain). A topical drop of 2% Methocel (OmniVision, Puchheim, Germany) was instilled in each eye before situating the corneal electrode.…”
Section: Erg Recordingsmentioning
confidence: 99%
“…Median, minimum, maximum, lower limit of reference interval, upper limit of reference interval, 90% CI for lower limit and 90% CI for upper limit are given. her flash intensity stimulations (Nair et al, 2011), but other investigators reported that volatile anesthetics generally had no noticeable effect on the ERG results (Ekesten, 2007). showed that a combination of xylazine and ketamine has the lowest impact on implicit times and amplitudes without ventral rotation of the eyeball and miosis.…”
Section: Ne Usmentioning
confidence: 98%
“…The determination of normal ERG values is of great importance for clinical practice, considering that there are numerous intrinsic and extrinsic factors influencing the ERG recordings including the age and breeds of the animal (Itoh et al, 2010), the environment and body temperature (Mizota and Adachi-Usami, 2002), pupil diameter, intraocular pressure and eye movement (Marmor et al, 2009;Grozdanic et al, 2010;Nair et al, 2011), electrode type and position (Mentzer et al, 2005), stage of retinal dark adaptation (Maehara et al, 2015), anesthesia technique (Norman et al, 2008;Lin et al, 2009). All of that contribute to interfere with the values obtained from ERG recording; therefore, the investigations aiming to establish a normal range still continue.…”
mentioning
confidence: 99%
“…Adult male Sprague-Dawley rats (∼300 g, N ¼ 3) were anesthetized with 1% isoflurane, paralyzed with 3.5 mg∕kg pancuronium bromide to prevent eye motion, 18 and mechanically ventilated. End-tidal CO 2 , heart rate, and oxygen saturation were monitored continuously and maintained within normal physiological ranges.…”
mentioning
confidence: 99%